STUDENTS' PERCEPTIONS OF DIFFICULTIES IN SPEAKING ENGLISH DURING ENGLISH CLASS AT SMP SWASTA KRISTEN BNKP GUNUNGSITOLI - Yestanius Waruwu; Trisman Harefa; Riswan Zega; Afore Tahir Harefa (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Speaking is one of the basic skills in learnng English that enables students to convey ideas and communicate effectively. However, many students still face difficulties in speaking due to various factors, such as lack of vocabulary, fear of making mistakes, and lack of confidence. This research aims to analyze students' perceptions and the factors affecting their difficulties in speaking English. This study used a qualitative descriptive method with data collected through questionnaires, interviews, and documentation. The research was conducted at the eighth grade of SMP Swasta Kristen BNKP Gunungsitoli with 18 students as participants. The findings revealed that students experienced various difficulties in speaking English, which were categorized into psychological problems (such as fear of making mistakes, shyness, anxiety, lack of confidence, lack of motivation, lack of pronounciation, and lack of vocabulary), language problems (including inhibition, nothing to say, low and uneven participation and the tendency to use mother tongue), and other influencing factors (such as physical condition, intelligence, aptitude, and interest). Most students showed lack of confidence and anxiety when speaking English, which led to limited participation during English class. The results of this study are expected to provide valuable insights for teachers to develop more effective and student-centered teaching strategies, and to create a supportive learning environment that encourages students to speak actively in English.